Clinical presentation and proteomic signature of patients with TANGO2 mutations. Issue 2 (13th August 2019) - Mingirulli, Nadja; Pyle, Angela; Hathazi, Denisa; Alston, Charlotte L.; Kohlschmidt, Nicolai; O'Grady, Gina; Waddell, Leigh; Evesson, Frances; Cooper, Sandra B. T.; Turner, Christian; Duff, Jennifer; Topf, Ana; et al.
Abstract: Transport And Golgi Organization protein 2 (TANGO2) deficiency has recently been identified as a rare metabolic disorder with a distinct clinical and biochemical phenotype of recurrent metabolic crises, hypoglycemia, lactic acidosis, rhabdomyolysis, arrhythmias, and encephalopathy with cognitive decline. We report nine subjects from seven independent families, and we studied muscle histology, respiratory chain enzyme activities in skeletal muscle and proteomic signature of fibroblasts. All nine subjects carried autosomal recessive TANGO2 mutations. Two carried the reported deletion of exons 3 to 9, one homozygous, one heterozygous with a 22q11.21 microdeletion inherited in trans . The other subjects carried three novel homozygous (c.262C>T/p.Arg88*; c.220A>C/p.Thr74Pro; c.380+1G>A), and two further novel heterozygous (c.6_9del/p.Phe6del); c.11‐13delTCT/p.Phe5del mutations. Immunoblot analysis detected a significant decrease of TANGO2 protein. Muscle histology showed mild variation of fiber diameter, no ragged‐red/cytochrome c oxidase‐negative fibers and a defect of multiple respiratory chain enzymes and coenzyme Q10 (CoQ10 ) in two cases, suggesting a possible secondary defect of oxidative phosphorylation. Proteomic analysis in fibroblasts revealed significant changes in components of the mitochondrial fatty acid oxidation, plasma membrane, endoplasmic reticulum‐Golgi network and secretory pathways. Clinical presentation of TANGO2 mutations is homogeneous and clinically recognizable. The hemizygous mutations in two patients suggest that some mutations leading to allele loss are difficult to detect. A combined defect of the respiratory chain enzymes and CoQ10 with altered levels of several membrane proteins provides molecular insights into the underlying pathophysiology and may guide rational new therapeutic interventions.